Analisa Kerusakan Roller Bearing pada Blower Induced Draft Fan Boiler Takuma pada Pabrik Kelapa Sawit XYZ - Simarmata, Firman Paniroi; Abdilah, Tomi; Suardi, Suardi (Rekayasa Material, Manufaktur dan Energi, 2026)
A steam boiler is an energy conversion machine that transforms water into steam through heating. The steam produced can drive a turbine, and the turbine then converts the thermal energy from the steam into mechanical energy. This mechanical energy is subsequently used to operate a generator. The boiler can operate properly with the support of several components, one of which is the fan, which provides thrust and air suction during the combustion process, thereby enhancing the performance of the power generation system. Fans are utilized to increase the efficiency of power plants because they maximize thrust at the fuel inlet channel, save fuel, and support complete combustion. Without a fan, it would be difficult to achieve thermal efficiency in the boiler. The Induce Draft Fan is a type of centrifugal blower whose rotating shaft is supported by roller bearings, which often encounter problems or failures. Damage to the roller bearing in the Induce Draft Fan will affect the blower’s performance; therefore, the author conducted an analysis of roller bearing failure on the Induce Draft Fan of the Takuma Boiler. The research method used is qualitative analysis, namely a study based on the systematic relationship between the variables under investigation. The aim of the analysis is to interpret the relationship among variables so that they can be used to answer the problems formulated in the study. The variables examined in this research are bearing vibration and bearing lubrication. The vibration data of the roller bearing on the Induce Draft Fan of the Takuma Boiler are as follows: outer axial position = 32.5 mm/s, inner axial position = 37.6 mm/s, outer vertical position = 15.8 mm/s, inner vertical position = 33.6 mm/s, outer horizontal position = 13.1 mm/s, and inner horizontal position = 49.9 mm/s. These values exceed the threshold limits of 7.10 mm/s and 11.20 mm/s (based on ISO 10816-1 vibration standards). Thus, the high vibration levels of the roller bearing in the Induce Draft Fan of the Takuma Boiler are the main factor causing premature bearing failure